A new genus and species of Baissidae in Late Cretaceous amber from New Jersey (Hymenoptera: Evanioidea) - Engel, Michael S. (Novitates Paleoentomologicae, 2013)
The extinct Mesozoic wasp family Baissidae is described from Late Cretaceous amber for the first time. Electrobaissa omega Engel, new genus and species, is described from an isolated male preserved in Turonian amber from New Jersey, and represents the latest occurrence of the family in the Mesozoic.